2010
DOI: 10.1007/s11095-010-0279-3
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Deep Percutaneous Penetration Associated with Anti-Inflammatory Activity of Topically Applied Helicteres gardneriana Extract: A Photoacoustic Spectroscopy Study

Abstract: This pre-clinical study showed the anti-inflammatory effect of Helicteres gardneriana extract. The photoacoustic technique was useful to demonstrate that this anti-inflammatory activity was associated with deep percutaneous penetration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Furthermore, treatment with the extract also inhibited the migration of polymorphonuclear cells but was not effective at reducing the number of mononuclear cells in the pleural cavity. Similarly, in previous studies, we found that the EEHg was also able to strongly reduce the migration of neutrophils in a mouse model of ear edema induced by croton oil, demonstrated by a reduction in myeloperoxidase activity [20]. …”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Furthermore, treatment with the extract also inhibited the migration of polymorphonuclear cells but was not effective at reducing the number of mononuclear cells in the pleural cavity. Similarly, in previous studies, we found that the EEHg was also able to strongly reduce the migration of neutrophils in a mouse model of ear edema induced by croton oil, demonstrated by a reduction in myeloperoxidase activity [20]. …”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, photoacoustic data showed that the strong anti-inflammatory effects of the extract were associated with the deep penetration observed for the extract [20]. In spite of these findings, no studies have evaluated the systemic anti-inflammatory effects of Helicteres gardneriana extract.…”
Section: Introductionmentioning
confidence: 99%
“…Croton oil was applied into both mouse's right and left auricles to induce inflammatory response, and the left auricle was treated with the extract. The strong anti-inflammatory effect observed for the Helicteres gardneriana extract was associated with the deep percutaneous penetration observed for the formulation, according to PA data (Melo et al, 2011).…”
Section: Measurements As a Function Of The Wavelength: Photoacoustic mentioning
confidence: 78%
“…By monitoring the PAS signal intensity with time in the UV (300-400nm) range, these authors demonstrated that dihydroxyacetone in combination with dimethylisosorbide enhances the process of tanning (Benamar et al, 2004). Recently, Melo et al (2011) applied PAS to evaluate the penetration rate of Helicteres gardneriana extract, topically applied for anti-inflammatory purposes. Experiments were conducted ex vivo in mice.…”
Section: Measurements As a Function Of The Wavelength: Photoacoustic mentioning
confidence: 99%
“…Biological studies have demonstrated that the extract of H. isora has antinociceptive, antidiabetic, hypolipidemic and hypoglycaemic activities (Chakrabarti et al, 2002;Kumar et al, 2006;Venkatesh et al, 2007;Bhavsar et al, 2009). The extract of Helicteres gardneriana leaf has been reported to possess antiprotozoal and antiinflammatory activity (Truiti et al, 2005;Oliveira de Melo et al, 2011), and the stem extract of H. hisuta exhibits cytotoxic activity against cancer cell lines (Chin et al, 2006).…”
Section: Introductionmentioning
confidence: 99%